Detection of serum anti-lipopolysaccharides (lps) antibodies from enterohemorrhagic e. coli (ehec) in asymptomatic kindergarten teachers of buenos aires province - Fernández Brando, Romina Jimena (2020)
EHEC is responsible for developing typical Hemolytic Uremic Syndrome (HUS) and Argentina has the highest incidence in the world. The endemo-epidemic behavior that HUS presents in our countrywas associated with person-to-person transmission. Since children below 5 years old are the most affected, our objective was to determine the frequency of kindergarten teachers with anti-LPS-EHECantibodies in serum. One hundred and fifty teachers from J.C. Paz district from Buenos Aires Province participated in an informative talk given by LuSUH, a non-governmental association, about good practices to reduce HUS transmission. Then, 63 of them voluntarily gave, under a signedwritten informed consent, a sample of blood obtained by finger puncture. A commercial ELISA (Chemtest, Arg) was used to detect specific IgM and IgG isotypes against 4 types of LPS-EHEC: O157, O145, O121 and O103. These variants represent approximately 87% of the EHEC serotypes associated with HUS in Argentina. The IgM finding was considered as indirect evidence of current infection with the EHEC specific serotype. Forty-two samples were evaluated, 60% (25/42) of them were positive for at least one type of LPS. Fifty-six percent of them (14/25) were IgM positive. Fifty percent of the positive samples were reactive for LPS O157, 26% for LPS O121, 12% for LPS O145 and 2% for LPS O103. Among the samples positive for LPS O157, 5% belonged to IgM isotype, 31% to IgG and 14% had both. The IgG isotype was the unique detected for LPS O145 and O103 (12 and2%, respectively). For LPS O121, the IgM isotype was detected in 2%, IgG in 12% and both isotypes in 12% of the samples. The elevated frequency of LPS-EHEC reactive samples (60%) reflects the high circulation of EHEC strains in our country. This agrees with the prevalence of anti-Stx2 antibodies reported in our population previously. Very strikingly, nearly half of these individuals carry IgM, suggesting that they would be in the active phase of infection.